THE IMPLEMENTATION OF SCIENTIFIC APPROACH USING DISCOVERY LEARNING IN TEACHING REPORT TEXT - Abdullah Azzam Akbar; Ahmad Syafi'i; Haris Dibdyaningsih (STKIP Al Hikmah Surabaya, 2023)
A newly designed curriculum called as K-13 (Curriculum 2013) was officially implemented in the beginning of 2013. A scientific approach becomes the most significant part of it. Five steps of scientific approach such as, observation, questioning, experimenting, associating and communicating will be studied in this research. One of the learning methods that is often used is discovery learning. This study aims to determine how the learning process uses the scientific approach with discovery learning methods in learning report text. Qualitative methods are used to see how this learning takes place. The research subjects were students of SMP IT Ibnu Sina grade 9. To obtain the data, observations, questionnaires and documentation were used. The results of the questionnaire showed that 5.26% (very positive), 56.39% (positive), 35, 33% (quite positive), and finally 3% (not positive). The analysis obtained shows that from the questionnaire given and the results of observations, students have very positive responses to learning using the scientific approach and discovery learning methods. But in practice it is not as easy as imagined. From 5 steps in the scientific approach, only 3 steps can be applied. This is influenced by learning that is carried out online. Suggestions that can be given are the teacher's ability to know what aspects must be considered before teaching and online learning must be better prepared because many materials are not easily explained without meeting students face to face.